إعداد معجم أحادي لكتاب اللغة العربية للصف الثاني عشر في مدارس إقليم كردستان العراق : دراسة معجمية - أمين، إسماعيل توفيق محمد
The he research aims to develop a monolingual dictionary for the twelfth preparatory grade book in the schools of the Kurdistan Region of Iraq, where the researcher collected vocabulary that is difficult to understand for high school students. There are two hundred and eighty-eight words from the Arabic language book for the twelfth grade of high school, and the researcher followed in his dictionary the alphabetical method without Stripping the words from their appendages with writing the root of the words next to them, then appending the past, present, infinitive, singular, plural and synonyms, and against the words, if any, as necessary. After that, the researcher tried to adequately explain the meaning of these words while coming up with useful phrases with citing a verse from the Holy Qur’an and a hadith from the Prophet’s hadiths at times, to help students understand in a realistic way. The researcher benefited from several ancient and modern dictionaries, including: (Kitab al-Ain, Tahdheeb Language, Dictionary of Language Measurements, Mukhtar al-Sahih, Lisan al-Arab, Ocean dictionary, Taj al-Arus, al-Munajd in the language, the intermediate dictionary, and the dictionary of contemporary Arabic). And the approach taken by the researcher is the descriptive and analytical approach. Among the most important findings of the researcher is the presence of difficult and laborious words in the prescribed curriculum and the necessity of having a dictionary to explain and clarify these words.